Out past the stars - Wagers, K. B. (The Farian war, 2021)
"When Hail confronts the Farian gods, the last thing she expected was to discover that they were part of a race of aliens who'd attacked the galaxy long before humanity's ancestors had crawled out of the sludge of Earth's oceans. The discovery carries with it dire news: The Hiervet, who'd once subjugated the mighty Svatir, are coming - a consequence of Hail's decision not to kill the Farian gods. Now the fate of the galaxy is on the line and Hail will have to make one final gamble to leverage chaos into peace"--